Global research progress in antibody-drug conjugates for solid tumors: Bibliometrics and visualized analysis - Wenjun Fang; Xueqing Ma; Ben Liu (Human Vaccines & Immunotherapeutics)
Recently, the use of antibody-drug conjugates (ADCs) in the research and management of solid tumors has increased, making them a key focus in the field of oncology. In this study, we performed a comprehensive literature review of ADCs use in solid tumor treatment. We retrieved data from the Web of Science Core Collection (WoSCC). Following literature retrieval, we conducted a thorough bibliometric and knowledge-mapping analysis of the collected articles. There was a rapid growth in the number of annual publications in this field. The United States had the highest publication volumes and led ADC research for solid tumors. Additionally, The Dana-Farber Cancer Institute had the highest output, and G. Curigliano was identified as the most productive author. The journal “Cancers” led in the publishing of ADC research on solid tumors. Furthermore, key clustering terms such as “breast cancer,” “targeted therapy,” “bladder cancer,” “ovarian cancer,” “expression,” and “drug delivery” emerged in this field as the research progressed. We identified six key themes by literature co-citation analysis, involving the research on the application of four ADCs in breast cancer, as well as the analysis of ADCs design, mechanisms, and strategies for reducing cytotoxicity. At the same time, based on the analysis of papers that have experienced a citation burst recently, we explored the future development trends of this field. Overall, our inaugural bibliometric analysis of ADCs for solid tumor research provides a systematic framework to guide future studies in this field. Therefore, facilitating and promoting further development in this area.